TM. Ali Muda (w. 2005 M) Karya dan Kontribusinya dalam Bidang Ilmu Falak - Arwin Juli Rakhmadi; Mario Kasduri; Muhammad Qorib; Habibullah Ritonga; Robie Fanreza; Abdul Rahman Cemda (Astroislamica: Journal of Islamic Astronomy, 2023)
TM. Ali Muda is a North Sumatran astronomy figure who came from Aceh. His work and contribution in the field of astronomy is beyond doubt. His thinking in the matter of determining the beginning of the month is to combine calculations and field observations. However, the tendency of his calculation (hisab) is also quite dominant which is shown by his analysis in various issues of celestial jurisprudence. Meanwhile, in the matter of matlak and Eid al-adha, the hajj-related services whose implementation is only in Mecca, according to him, are obliged to hold on to the matlak of Mecca, while those whose implementation is not only in Mecca are obliged to hold on to their respective matlak